2020
DOI: 10.1177/0146167220928238
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Solitude After Being Ostracized: A Replication and Beyond

Abstract: Individuals may respond to ostracism by either behaving prosocially or antisocially. A recent paper provides evidence for a third response: solitude seeking, suggesting that ostracized individuals may ironically engage in self-perpetuating behaviors which exacerbate social isolation. To examine this counterintuitive response to ostracism, we conceptually replicated the original paper in three studies ( N = 1,118). Ostracism experiences were associated with preference for solitude across four samples (Study 1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 76 publications
1
33
0
Order By: Relevance
“…Targets of ostracism may withdraw from social interactions to minimize risk of additional social pain (Richman & Leary, 2009;Van Kleef et al, 2010). In past experiments, targets of ostracism (vs. inclusion) indicated stronger intentions to disengage from social situations (Pfundmair et al, 2015), more positive ratings of physical spaces that hinder social interaction (Meagher & Marsh, 2017), and, importantly, a higher preference for being alone in the following activity (Ren et al, 2020). Here, we showed that, ironically, the very response to ostracism (i.e., preference for solitude) may put targets at higher risk for ostracism in future social interactions.…”
Section: Theoretical Contributionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Targets of ostracism may withdraw from social interactions to minimize risk of additional social pain (Richman & Leary, 2009;Van Kleef et al, 2010). In past experiments, targets of ostracism (vs. inclusion) indicated stronger intentions to disengage from social situations (Pfundmair et al, 2015), more positive ratings of physical spaces that hinder social interaction (Meagher & Marsh, 2017), and, importantly, a higher preference for being alone in the following activity (Ren et al, 2020). Here, we showed that, ironically, the very response to ostracism (i.e., preference for solitude) may put targets at higher risk for ostracism in future social interactions.…”
Section: Theoretical Contributionsmentioning
confidence: 98%
“…Measures of preference for solitude, ostracism experience, and the Big Five traits were embedded in this survey. Participants in the Dutch-language sample completed translated versions of these measures: The Dutch version of the preference for solitude and ostracism experience measures were obtained from Ren & colleagues (2020) ; the Dutch version of the Big Five measure was obtained from Denissen & colleagues (2008) .…”
Section: Studies 1 Andmentioning
confidence: 99%
“…Moreover, being included by more group members in a group interaction decreased aggression, but each additional "includer" has a smaller incremental effect for reducing aggression (DeWall et al, 2010). Finally, being socially included in an interaction resulted in more positive outcomes, as compared to being excluded; but being overincluded (e.g., being included to a greater extent than other group members) did not result in higher levels of positivity (Ren et al, 2021;van Beest & Williams, 2006;Wolf et al, 2015;Williams, Cheung, & Choi, 2000).…”
mentioning
confidence: 99%
“…Recent examples include Bergfeld & Chiu (2017), Brooks et al (2019), Irwin et al (2019), Schroeder et al (2019, and Ren et al (2020), among many others. Possible reasons may be that the mediators were contemporaneously measured, or there was simply insufficient theoretical or experimental justification to warrant positing a causal structure among the mediators.…”
Section: Practical Considerations For Applied Researchersmentioning
confidence: 99%